Pengaruh Metode Latihan Bent Arm Pullover and Press dan Power Otot Lengan Terhadap Hasil Lempar Lembing (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2007)
Objectives: The purpose of this study was to detect: (1) difference between practice method bent arm pullover and press according to non linear and linear towards result throws javelin, (2) interaction between practice method and power arm muscle towards result throws javelin, (3) difference between practice method bent arm pullover and press according to non linear and linear in sample that has power arm muscle very good towards result throws javelin, (4) difference between practice method bent arm pullover and press according to non linear and linear in sample that has power arm muscle less towards result throws javelin. Methods: 40 person taken by purposive samples based on power arm muscle very balk and less. This study uses experiment method with factorial block 2x2 design. Instrument in this Study: (1) test has throwed medicine ball that is tool to measures ability power student university arm muscle that tested level reliabilitas as big as (r = 0,90 (2), tests throws javelin to measures result throw javelin, that tested level reliabilitas as big as (r = 0,94 (3), practice programs bent arm pullover and press according to non linear and linear. Analysis technique that used analysis variant two directions (two-way anava) continued with test tukey in standard significant = 0,05. Results: (1) found difference between practice method bent arm pullover and press according to non linear and linear towards result throws javelin, (2) found interaction between practice method ably power arm muscle towards result throws javelin, (3) found difference between practice method bent arm pullover and press according to non linear and linear in group power arm muscle very good towards result throws javelin, (4) found difference between practice method bent arm pullover and press according to non linear and linear in group power arm muscle less towards result throws javelin.Keywords: Exercise, Muscle Power, Bent Arm Pullover